The clinicopathological spectrum and driver mutation profile in classic BCR-ABL1 negative myeloproliferative neoplasms: a three-year study from a tertiary care center in Kerala, South India - Surendran, Subha M.; Paul, Mobin; D’souza, Chryselle O.; Abraham, Latha K. (International Journal of Research in Medical Sciences, 2024)
Background: Myeloproliferative neoplasms (MPNs) are clonal hematopoietic stem cell disorders primarily of the adults. The 2016 World Health Organization (WHO) classification of MPNs include the molecular landscape as one of the diagnostic criteria. JAK2 exon14 (JAK2 V617F), JAK2 exon12, Myeloproliferative leukemia virus oncogene exon 10 (MPL 515), and calreticulin exon 9 (CALR) mutations are the main somatic driver mutations detected in classic BCR-ABL1 negative MPNs. Methods: A retrospective, cross-sectional study was conducted including 99 patients diagnosed with classic BCR-ABL1 negative MPNs during a 3-year time period, from March 2018 to February 2021 in the departments of pathology and clinical haematology- haemato oncology of a tertiary care teaching hospital. Clinical, haematological and morphological features were analysed and correlated with MPN associated mutation studies done in blood/bone marrow samples. Results: The prevalence of polycythaemia vera (PV) was found to be higher than other MPN, two third of which were JAK2 positive. More than half of the cases of primary myelofibrosis (PMF) and essential thrombocythemia (ET) also showed JAK2 mutation. CALR was positive in 17.4% of ET and 31.3% of PMF; MPL in 4.4% of ET and 3.1% of PMF. Conclusions: The prevalence of triple-negative MPN point towards the need for whole-exome sequencing of triple-negative MPN.